Awareness Of Applying Lean Construction In Penang, Malaysia - Goh, Poi See (Universiti Sains Malaysia, 2005)
The findings arc documented as a result of awareness of applying lean construction in Penang, Malaysia. The questionnaire returned by those construction firms that responded was tabulated and analyzed, results of which from the main core of this study. Lean Construction concepts and principles innovate an efficient management of construction processes. The survey indicates that all firms have performed most of the instruments and integrated the Lean Construction principles into their activities. Some of the principles and instruments are applied more frequently than others. In the survey, this study focuses on the need, concept and essential tools for the development of construction companies through a proper application of Lean Construction.